Immunological Differences in Human Peripheral Blood Mononuclear Cells Treated with Traditional Japanese Herbal Medicines Hochuekkito, Juzentaihoto, and Ninjin'yoeito from Different Pharmaceutical Companies. (20th September 2021) - Kiyomi, Anna; Matsuda, Ayaka; Nara, Moeko; Yamazaki, Kyosuke; Imai, Shinobu; Sugiura, Munetoshi
Abstract : Hochuekkito (HET), Juzentaihoto (JTT), and Ninjin'yoeito (NYT) have been used as Hozai, a group of traditional Japanese herbal medicines, to treat physically and mentally weak cancer patients. Their compositions are quite different, and Japanese pharmaceutical companies have been using different types or quantities of herbs for formulations with the same name. Here, we compared the immunological differences between HET, JTT, and NYT with respect to the induced T cell subsets and cytokines. Peripheral blood mononuclear cells (PBMCs) were isolated from healthy volunteers and treated with 0 (control), 25, 50, 100, 200, or 400  μ g/mL HET, JTT, or NYT (manufactured by Tsumura [TJ], Kracie [KR], and Kotaro [KO]). PBMC proliferation, CD4 + T cell, CD8 + T cell, and regulatory T cell (Treg) proportions and interleukin (IL) concentrations (IL-6, IL-10, IL-17A, interferon- γ, tumor necrosis factor- α, and transforming growth factor (TGF)- β ) secreted by PBMCs were measured using Cell Counting Kit-8 or flow cytometry bead analysis. PBMC proliferation and CD4 + T cell percentages were similar in the HET, JTT, NYT, and control groups; however, the percentage of CD8 + T cells tended to increase after treatments. Tregs were suppressed by HET, JTT, and NYT, and TJ-JTT significantly decreased Treg numbers (compared with control). The concentrations of all cytokines except TGF- β were increased in a concentration-dependent manner (p < 0.05 ); particularly, KR-HET induced IL-6 secretion (compared with the control, TJ-HET, and KO-HET; 37-, 7-, and 17-fold, respectively; p < 0.05 ). The TGF- β concentration was decreased in a concentration-dependent manner by HET, JTT, and NYT (compared with the control). These results suggest that, compared with TJ-HET and KO-HET, KR-HET should be administered with caution. Although HET, JTT, and NYT belong to the same Hozai group and have the same names among companies, their differing effects on immune activity must be considered and they must be administered with caution.